Proteomic study of in vitro osteogenic differentiation of mesenchymal stem cells in high glucose condition - Kuneerat Aswamenakul (2020)
© 2020, Springer Nature B.V. Patients with diabetes have been widely reported to be at an increased risk of secondary osteoporosis. Osteoporosis is caused by an imbalance in bone remodeling due to increased bone resorption and/or decreased osteoblast-dependent bone formation. In this study, mesenchymal stem cells (MSCs) were used as a disease model to determine the effects of high glucose levels on MSC-osteoblast development. The results indicated that under high glucose conditions, MSCs had reduced cell viability and increased number of β-galactosidase-positive cells. Furthermore, in vitro osteogenesis was shown to be reduced in MSCs cultured in osteogenic differentiation medium at 10, 25, and 40 mM glucose as demonstrated by Alizarin red S staining and alkaline phosphatase activity assay. Moreover, a proteomic study was performed in MSCs cultured with 25 and 40 mM glucose. The proteomic results demonstrated that 12 proteins were up- and downregulated in bone marrow-derived mesenchymal stem cells cultured with high glucose in a dose-dependent manner. The findings presented here contribute to our understanding of the mechanism of diabetes mellitus responsible for bone loss. However, the exact mechanism of action of hyperglycemia on bone deformability requires additional studies.